Mathematical model of welding parameters for rapid prototyping using robot welding - Ogunbiyi, Babatunde (1997)
Rapid Prototyping is a relatively new technology that allows the creation of prototypes in a very short period of time compared with traditional manufacturing techniques. First, a model of the prototype is drawn, using a computer aided design program, which is then mathematically ‘sliced’ and used to build the prototype layer by layer, using material such as paper, resins, or thermoplastics, depending on the process. The main disadvantage of these processes is that they do not allow metal as a raw material. Rapid Prototyping using Robot welding is another approach that overcomes this problem by using a welding robot that deposits metal. As the success of the final component quality depends very much on the welding parameters, it is important to automate their calculation. To automate the task of determining the welding parameters and to generate welded components with consistent quality, a very simple mathematical algorithm was created. The tests carried out to gather the necessary information to generate this model, the mathematical model itself, the limitations of the equations, and the tests to check their feasibility are described. At the time the work was carried out, the authors were in the welding Engineering Groups, SIMS, Cranfield University, Cranfield, Beds. MK43 0SY, UK. Dr Ribeiro is now in the Department of Industrial Electronics, University of Minho, 4800 Guimarães, Portugal and Professor Norrish is in the Faculty of Engineering, University of Wollongong, Wollongong, NSW 2522, Australia. Manuscript received 12 May 1997; in final form 20 June 1997.